DOM hydrophilic components of organic fertilizers increased the soil nitrogen retention capacity and succession of the microbial community - Wang, Yuyun; Ge, Yingtong; Deng, Yaqin; Xu, Xiang; Zhang, Yong; Li, Lan; Xu, Zhi (Frontiers in Microbiology, 2023)
Application of organic fertilizers affects soil properties and microbial communities, which in turn alters soil N transformation processes. Unfortunately, it is not clear how the difference in the character of the organic fertilizer DOM affects the soil nitrogen retention capacity and its microbial processes. According to the principle of equal nutrients, the treatments of chemical fertilizer alone (treatment CF), chemical fertilizer with organic fertilizer DOM hydrophilic components (treatment H), and chemical fertilizer with organic fertilizer DOM hydrophobic components (treatment P) were set up, where the characteristics of soil nitrogen transformation and changes in microbial community structure were studied with soil culture conditions for 24 days. It was discovered that the addition of organic fertilizer DOM components (H and P) slowed nitrification rate and increased protease activity resulting in a higher NH4 + -N content compared to the CF treatment. The DOM addition (H and P) increased the microbial biomass nitrogen (MBN) levels in the soil and increased the soil nitrogen pool capacity. Moreover, the carbon use efficiency of the hydrophilic components is higher than that of the hydrophobic components, resulting in its further increase in nitrogen reservoir capacity and higher nitrogen retention capacity. Network analysis showed that the addition of organic fertilizer DOM hydrophilic components increased network complexity and synergy between microorganisms. In combination with random forest analysis, it was shown that Sphingomonas and Massilia were key species influencing soil nitrogen retention capacity and nitrogen availability characteristics.